Determination of basic calculation and experimental parameters of device for bore hole cleaning - Davydenko, O; Ratov, B; Ighnatov, A (National Mining University, 2016)
Purpose. To substantiate the design and operating technological parameters of the device for the interval bore hole cleaning departing from the set dependences of active jets formation in the flow through the blade element. Methods. Application of bench and analytical research techniques allowed to establish the fundamental principles of active jets formation in the flow through the blade element of the designed device and the nature of their impact on the processed objects. Findings. Bench testing of the device for the interval bore hole cleaning resulted in defining aspects of the mechanism of active fluid jets formation. We studied the distribution of speed components in the workflow. The use of tilted surface for the formation of the blade profile has been justified. As a result of studying the physical model of the device working body, we received data regarding its structural design. Information about the peculiar hydrodynamics of the flow around the blade node with respect to the process of removing clay-mud agglomerates has been provided. The indicators of the effectiveness of the designed device were designated. Originality. The steady flow through the blade element and consequently the removal of clay-mud agglomerates is provided by well-defined structural design characteristics which determine hydrodynamic aspects of the unit operation. Practical implications. The results of laboratory and analytical studies are the base for designing the operating parameters of the process of preparing a bore hole for casing running and subsequent plugging of the bore hole with a guaranteed provision of high technical and economic indicators. Data for the study of the flow mode through the blade element are the basis for the hydrodynamic calculation of the device for the interval cleaning.

Мета. Обґрунтування конструктивного виконання технологічних і режимних параметрів роботи пристрою поінтервального очищення стовбура свердловини виходячи із встановлених закономірностей формування активних струменів рідини при обтіканні лопатевого елемента. Методика. Стендовими і аналітичними прийомами досліджень встановлені основні принципи формування активних струменів при обтіканні лопатевого елемента проектованого пристрою і характер їх впливу на об’єкти обробки. Результати. В результаті проведення стендових досліджень пристрою поінтервального очищення стовбура свердловини встановлені аспекти механізму формування активних струменів рідини. Вивчено розподіл швидкісних складових в робочому потоці. Обґрунтовано застосування гвинтової поверхні для утворення контуру лопаті. На основі розгляду фізичної моделі робочого органу пристрою отримані дані щодо його конструктивного оформлення. Наведено відомості про особливості гідродинаміки обтікання лопатевого вузла стосовно процесу видалення шламових скупчень. Визначені показники результативності застосування проектованого пристрою. Наукова новизна. Стійкому режиму обтікання лопатевого органу і як наслідок видалення шламових скупчень відповідають цілком певні конструктивні характеристики, що визначають гідродинамічну сторону функціонування пристрою. Практична значимість. Отримані результати лабораторних та аналітичних досліджень є базовими для проектування режимних параметрів процесу підготовки свердловини до спуску обсадної колони і подальшого тампонування стовбура з гарантованим забезпеченням високих техніко-економічних показників. Дані по вивченню режиму обтікання лопатевого елемента являють собою основу гідродинамічного розрахунку пристрою поінтервального очищення.

Цель. Обоснование конструктивного исполнения и режимных технологических параметров работы устройства поинтервальной очистки ствола скважины, исходя из установленных закономерностей формирования активных струй жидкости при обтекании лопастного элемента. Методика. Стендовыми и аналитическими приемами исследований установлены основополагающие принципы формирования активных струй при обтекании лопастного элемента проектируемого устройства и характер их воздействия на объекты обработки. Результаты. В результате проведения стендовых исследований устройства поинтервальной очистки ствола скважины установлены аспекты механизма формирования активных струй жидкости. Изучено распределение скоростных составляющих в рабочем потоке. Обосновано применение винтовой поверхности для образования контура лопасти. На основе рассмотрения физической модели рабочего органа устройства получены данные относительно его конструктивного оформления. Приведены сведения об особенностях гидродинамики обтекания лопастного узла применительно процессу удаления шламовых скоплений. Обозначены показатели результативности применения проектируемого устройства. Научная новизна. Устойчивому режиму обтекания лопастного органа и как следствие удаления шламовых скоплений соответствуют вполне определенные конструктивные характеристики, определяющие гидродинамическую сторону функционирования устройства. Практическая значимость. Полученные результаты лабораторных и аналитических исследований являются базовыми для проектирования режимных параметров процесса подготовки скважины к спуску обсадной колонны и последующему тампонированию ствола с гарантированным обеспечением высоких технико-экономических показателей. Данные по изучению режима обтекания лопастного элемента представляют собой основу гидродинамического расчета устройства поинтервальной очистки.
Keywords: bore hole; vugg; clay-mud agglomerates; device for cleaning; drilling fluid; active jet; flow rate